A Study of Specific Dermatoses and Skin Disease Affected by Pregnancy - Samina Naz, Seemab Khan, Monika, Sughra Abbasi, Yasmeen, Romasa Muzaffar Ali Joyo, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Pregnancy associated skin diseases or changes can be physiological (hormonal), skin pre-existing disease, and development of dermatoses with new pregnancy. The specific skin dermatoses related to pregnancy involve eruption of pruritic skin in poorly defined heterogeneous group. The present study aimed to evaluate the specific dermatoses and skin disease affected by pregnancy. Methodology: This cross-sectional study was carried out on 226 pregnant women in the department of Obstetrics and Gynecology of Murshid Hospital and Health Care Centre, Karachi from January 2018 to June 2019. All the patients were investigated for pregnancy associated cutaneous changes. The presence of any concomitant dermatoses that developed during pregnancy was investigated. Detailed clinical examination was performed on pregnant women with specific dermatoses of pregnancy regarding pattern, distribution, and morphology of lesions. All the pregnant women undergone through routinely blood investigation. Results: Of the total 226 pregnant women, the incidence of specific dermatosis during pregnancy was 27 (11.95%). Prurigo of pregnancy was the prevalent specific dermatosis of pregnancy in 13 (5.8%) cases. The incidence of intrahepatic cholestasis of pregnancy (ICP), pruritic urticarial papules and plaques of pregnancy (PUPP), and pruritic folliculitis of pregnancy (PFP) was 6 (2.7%), 5 (2.2%), and 3 (1.3%) respectively. All these skin diseases were caused by pregnancy in 11.95% of females. Conclusion: The present study found that Prurigo of pregnancy was the prevalent dermatosis of pregnancy that occurred in the multigravida second trimester. The rare dermatosis with no primary lesion was intrahepatic cholestasis of pregnancy. The course of pregnancy-associated disease changes, in turn, causes exacerbation like psoriasis, vitiligo, and dermatosis. Keywords: Specific Dermatoses, Skin disease, Pregnancy